Implementation of Experiential Learning to Enhance Students' Historical Thinking Skills - Firmansyah, Haris; Eka Putri, Astrini; Wiyono, Hadi (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study explores the implementation of Experiential Learning in enhancing students' historical thinking skills. Historical thinking is a critical competency that enables students to analyze, interpret, and critically evaluate historical events, moving beyond rote memorization. However, history education in Indonesia is predominantly lecture-based, limiting student engagement and analytical skill development. This research adopts a qualitative case study approach conducted at a high school in Pontianak, involving history teachers and students. Data were collected through in-depth interviews, participant observations, and document analysis. The findings indicate that Experiential Learning, through methods such as historical field trips, reenactments, and project-based learning, significantly improves students' chronological understanding, awareness of historical causation, and empathy for historical figures. The study also identifies challenges, including resource constraints and the need for more effective instructional strategies. The research concludes that Experiential Learning promotes a deeper, more meaningful understanding of history, empowering students to construct knowledge through firsthand experiences actively. Future research should focus on developing scalable models for integrating Experiential Learning in diverse educational settings.